1990
DOI: 10.1111/j.1600-0722.1990.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of dental gels containing combinations of amine fluoride, stannous fluoride, and chlorhexidine against cariogenic bacteria

Abstract: – The in vitro susceptibility of Streptococcus mutans, S. sobrinus and Lactobacillus casei to dental gels containing various combinations of amine fluoride (AmF 297), stannous fluoride (SnF2), and chlorhexidine (CHX) was studied. The combination of AmF‐SnF2 with a total fluoride content of 1.2% was the most effective against mutans streptococci but not against L. casei. At notably lower total fluoride concentration (0.4%), AmF as such or combined with SnF2, was significantly less effective against mutans stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…Although in vitro tests have shown SnFo-AmF gel to be even slightly niore potent inhibitor o^Streptococcus mutans and S. sobrinus than chlorhexidine (17), the in vivo situation was not the same. SnF.,-AmF gel was significantly antistreptococcal but less effective than chlorhexidine.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Although in vitro tests have shown SnFo-AmF gel to be even slightly niore potent inhibitor o^Streptococcus mutans and S. sobrinus than chlorhexidine (17), the in vivo situation was not the same. SnF.,-AmF gel was significantly antistreptococcal but less effective than chlorhexidine.…”
Section: Discussionmentioning
confidence: 89%
“…Because stannous fluoride (SnF9; 5,13,14) and amine fluoride (AmF; 15) also exhibit .significant antibacterial properties against oral mutans streptococci and lactobacilh, their combination has been studied as a possibility to combat oral cariogenic bacteria (16,17). Although in vitro studies have shown SnFj-AmF combinations to be as effective as GHX against mutans streptococci (16,17), SnF,-AmF solution with a low total F~ content (0.025%) did not prevent plaque accumulation, nor the growth of oral mutans streptococci (18). This was clearly in contrast to a GHX solution (0.12%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] TTO shares a similar range of antimicrobial activity with chlorhexidine (CHX), although their mechanisms of action differ. 9,[12][13][14][15][16][17][18] They both have antibacterial, antiviral and antifungal properties. TTO has the potential to be a therapeutic agent in chronic gingivitis and periodontitis, conditions that have both bacterial and inflammatory components.…”
mentioning
confidence: 99%
“…It was also published that the effect of CHX gel is increased with combined use of fluoride gel (Ostela & Tenovuo, 1990;Meurman, 1988). In addition to the antibacterial CHX (0.11%), Cervitec gel (Vivadent, Schaan, Liechtenstein) containing fluoride (900 ppm) which promotes remineralization and protects the teeth from caries.…”
Section: Chlorhexidine Gelsmentioning
confidence: 99%